2021
DOI: 10.1093/gbe/evab090
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Analyses Unveil Helmeted Guinea Fowl (Numida meleagris) Domestication in West Africa

Abstract: Domestication of the helmeted guinea fowl (HGF; Numida meleagris) in Africa remains elusive. Here we report a high-quality de novo genome assembly for domestic HGF generated by long- and short-reads sequencing together with optical and chromatin interaction mapping. Using this assembly as the reference, we performed population genomic analyses for newly sequenced whole-genomes for 129 birds from Africa, Asia, and Europe, including domestic animals (n = 89), wild progenitors (n = 34), and their closely related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…With the improvement of whole-genome sequencing technology, an increasing number of avian genomes are being assembled, such as Numida meleagris [ 7 ], Phasianus colchicus [ 8 ], and Fringilla coelebs [ 9 ], which provide basic references for the study of phenotypic characteristics, evolution, economic traits, and environmental adaptation of birds [ 10 ]. Comparative genomics analysis is an important tool for revealing the adaptive evolution, phenotypic evolution, and genome characteristics of species [ 11 ], and it is widely applied to studies of the evolution and origin of animals or plants [ 12–14 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of whole-genome sequencing technology, an increasing number of avian genomes are being assembled, such as Numida meleagris [ 7 ], Phasianus colchicus [ 8 ], and Fringilla coelebs [ 9 ], which provide basic references for the study of phenotypic characteristics, evolution, economic traits, and environmental adaptation of birds [ 10 ]. Comparative genomics analysis is an important tool for revealing the adaptive evolution, phenotypic evolution, and genome characteristics of species [ 11 ], and it is widely applied to studies of the evolution and origin of animals or plants [ 12–14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics suggested the use of whole eggs from the helmeted guinea fowl (Numida meleagris) and wild turkey (Meleagris gallopavo), which were found together in the red sample from the Fish mask. The helmeted guinea fowl is native to Burkina Faso (Appendix A) and genomic studies showed that it was domesticated in West Africa around 1300-5500 years ago [31]. The turkey is native to central Mexico, but during the Spanish colonization, it was imported to Europe and then distributed in the 17th century across other continents, including Africa [32].…”
Section: Discussionmentioning
confidence: 99%
“…In wild populations, an improved genome assembly can also help in capturing population-specific variation that could be used in the design of conservation programs. So far, in the Galliformes, the genome assemblies of the chicken 7,8 , Japanese quail (Coturnix japonica) 9,10 , Gunnison sage-grouse 11 , helmeted guineafowl 12 , and turkey 13 are high-quality genome assemblies based on long-read sequencing technology. These high-quality assemblies allow for comparative studies within the Galliformes and raise the opportunities for further research.…”
Section: Background and Summarymentioning
confidence: 99%